Analysis of the Business Environment in Formulating Marketing Strategy and The Impact on Sales and Financial Performance in the Post COVID 19 Pandemic - Syaifuddin , Syaifuddin (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The current environmental changes as a result of the COVID-19 pandemic and entering the "new normal era" require companies to adapt business and marketing strategies that are appropriate and effective. Companies should formulate appropriate marketing strategies to gain competitive advantages and win the market. The purpose of this research is to determine the role of the external and internal environments in marketing strategy formulation and its impact on sales performance. This research is conducted by using descriptive and explanatory survey methods. The tool of analysis is the structural equation model. The unit of analysis is the creative industry in Bandung, while the unit of observation is the management. The sampling technique used is stratified random sampling. The characteristics are measured from each respondent's external environment, internal environment, marketing strategy, and sales performance. The results show that the external environment as well as the internal environment affect marketing strategy and sales performance significantly